Biocompatibilidade de scaffolds nanofibrosos contendo metronidazol ou ciprofloxacina em modelo de implantação subcutânea em ratos - Passos, Patrícia Cabral (2016)
Evidence shows there is no ideal membrane, i.e., biocompatible, biodegradable, with adequate mechanical and physical properties that enable reorganization of periodontal tissues. Eletrospinning technique has demonstrated good processing results on scaffolds made from polymers. Nanofibrous formed by this technique have characteristics that resemble the extracellular matrix. The aim of this study was to evaluate the biocompatibility of nanofibrous polydioxanone scaffolds (PDS II®) containing metronidazole or ciprofloxacin in subcutaneous implantation model in rats Wistar. PDS II® is biocompatible polyester having various applications in the medical field. Our conceptual hypothesis considers that scaffolds with antimicrobials have similar inflammatory behavior when compared to PDS positive control. Sixty adult male rats were randomized into 6 groups: negative control (SHAM) animals with incision and surgical pocket, without scaffold; positive control (PDS) animals with PDS scaffolds; 1MET animals with one PDS scaffold containing 25%wt metronidazole; 2MET animals with two PDS scaffolds containing 25%wt metronidazole, 1CIP animals with PDS scaffolds containing 25%wt ciprofloxacin; 2CIP animals with two PDS scaffolds containing 25%wt ciprofloxacin. Animals were euthanized at 3 days (n=30) and 30 days (n=30), corresponding to initial and late inflammatory responses, respectively. Outcomes measures were the degradation of collagen fibers (Picrosirius Red and Masson´s trichrome), activity of cellular enzyme (Myeloperoxidase activity and N-acetyl-β-D-glucosaminidase activity) and local oxidative profile (reactive oxygen species, lipid peroxidation, protein carbonyl, vitamin C, catalase and reduced glutathione). Dara were analyzed statistically (p<0.05) by two-way ANOVA (treatment and time). Collectively, results show that antibiotics scaffolds have a lower inflammatory response compared to PDS group. Among the nanofibers with antibiotics, the group showed better early and late inflammatory response was 2CIP. The findings of this research suggest the potential study of these scaffolds with metronidazole and ciprofloxacin in regenerative models, able to confirm the effectiveness of these artificial matrices for periodontal regeneration.